Flexibility in IT Project Management: A Case Study of CRM Implementation - Przybylska-Curyl, Natalia (Elastyczność w zarządzaniu projektami IT: studium przypadku wdrożenia CRM, 2024)
Aim: This article aims to elucidate the significance of flexibility in IT project management. The article emphasises the necessity for adaptation to evolving market conditions, encompassing legal developments, technological innovations and intensifying competition. Methodology: The article employs a case study methodology which allows for a comprehensive examination of intricate processes within their intrinsic context. An analysis of the literature on the subject was also conducted. Results: Implementing a customer relationship management (CRM) system exemplifies the application of the SCRUM methodology, which facilitates flexibility, enabling more expedient responses to changes while maintaining budgetary constraints and project deadlines and ultimately achieving customer satisfaction. Implications and recommendations: Implementing the SCRUM methodology in the context of IT project management facilitates flexibility and adaptation to evolving market demands, thereby contributing to the success of projects. Originality/value: The article underscores the significance of identifying an optimal project management methodology in light of the necessity for flexibility. It illustrates the pragmatic application of the SCRUM methodology in implementing a customer relationship management (CRM) system.
Business Informatics = Informatyka Ekonomiczna, 2024, Nr 1-2 (67-68), s. 75-84
Keywords: agile project management; CRM implementation; IT flexibility; project adaptability; zarządzanie projektami Agile; wdrożenie CRM; elastyczność w IT; adaptacja projektów